PERCEPTION OF THE FARMERS TOWARDS NEEM COATED UREA IN PRAKASAM DISTRICT OF ANDHRA PRADESH - SARADA, O. (The Journal of Research, PJTSAU, 2019)
In fact, the use of chemical fertilizers in India over the last 50 years has grown nearly 170 times (FAO, 2006).The most common nitrogenous fertilizer, Urea, with the highest nitrogen content (46 per cent), isused widely across the countries of the world as the main source of critical nutrient for crop growth. As per research findings, nitrogen from urea is released in the soil and water and is leached by the activity of nitrifying bacteria, Nitrobacteria and Nitrosomonas. These bacteria turn nitrogen into nitrite and then to nitrate which are highly mobile in nature when present in soil. In the process, approximately fifty per cent of the applied nitrogen in urea is lost through leaching into the soil, causing extensive ground water contamination. Neem coated urea (NCU) is a solution to the problem, preventing the bacterial activity of nitrification. Recent research indicates that ‘sustained release’ nature of Neem Coated Urea has resulted in reasonable increase in rice yield by 9.6 per cent and wheat yield by 6.9 per cent.